2009
DOI: 10.3892/mmr_00000119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol, progesterone and testosterone on apoptosis- and proliferation-induced MAPK signaling in human umbilical vein endothelial cells

Abstract: Abstract. Sex hormones induce death or cell proliferation in various cell lines and in primary cultures. However, the signal transduction pathways involved in the regulation of proliferation and apoptosis in endothelial cells have not been fully elucidated. Here, we report that progesterone and testosterone induce apoptosis in HUVECs in a p38-and JNK-dependent manner, and that estradiol promotes proliferation via the activation of ERK2. We showed that, at physiological doses, progesterone and testosterone prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…As the ovarian cancer cells tested lack PR, the authors suggest P4 is functioning through MPRs. Treatment of human umbilical vein endothelial cells with supraphysiological levels of P4 was able to induce JNK phosphorylation, but JNK activation was not evident at physiological concentrations (Powazniak, Kempfer, de la Paz Dominguez et al, 2009). Studies evaluating P4 effects on epidermal growth factor (EGF) signaling in breast cancer cells revealed treatment of T47D-YB cells with R5020, a P4 agonist, for 48 h prior to EGF treatment resulted in JNK phosphorylation (Lange, Richer, Shen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As the ovarian cancer cells tested lack PR, the authors suggest P4 is functioning through MPRs. Treatment of human umbilical vein endothelial cells with supraphysiological levels of P4 was able to induce JNK phosphorylation, but JNK activation was not evident at physiological concentrations (Powazniak, Kempfer, de la Paz Dominguez et al, 2009). Studies evaluating P4 effects on epidermal growth factor (EGF) signaling in breast cancer cells revealed treatment of T47D-YB cells with R5020, a P4 agonist, for 48 h prior to EGF treatment resulted in JNK phosphorylation (Lange, Richer, Shen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The present study examined the possible mechanism underlying the action of periostin in endothelial cells. Previous studies revealed that growth factors stimulate angiogenesis via activating kinase signaling pathways, including PI3K/AKT, ERK1/2, FAK and p38/MAPK, to regulate endothelial cell migration, survival and vascular permeability ( 28 , 29 ). In the present study, periostin promoted HUVEC migration and tube formation by activating the ERK1/2 and FAK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Rat CMECs cultured for 48 h in hormone-free medium were plated at ~90% confluent in 24-well culture plates. After 12 h, the cell monolayer was scraped with a 1-ml pipette tip to create a cell-free zone [ 6 ]. The medium and dislodged cells were then aspirated, and the plates were rinsed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Powazniak et al demonstrated that estradiol enhanced human umbilical vein endothelial cell activity (non-endometrial endothelial cells) in vitro and in vivo [ 6 ]. These cells play an important role in neovascularization, suggesting a promoting influence of estrogen on angiogenesis.…”
Section: Introductionmentioning
confidence: 99%